Cadaveric study of the origin, course, branching pattern, and termination of the left coronary artery in Indian population: An observational study. - Bang, Swati; Patil, Anjali Gopalrao (Journal of Neonatal Surgery, 2025)
Background: The heart functions as a vital organ by pumping blood to all body tissues through the aorta. Its muscular wall (myocardium) receives oxygen and nutrients from the coronary arteries, which are divided into right and left coronary arteries. Methods: A total of 50 adult human heart specimens were included in the study. The specimens were obtained from deceased individuals subjected to routine cadaveric dissection for undergraduate (MBBS) teaching purposes in the Department of Anatomy, Index Medical College Hospital & Research Centre (IMCH & RC), Indore. We proceeded to investigate the branching pattern of the LCA. Throughout their whole course, from the point of origin to the point of termination of LCA was tracked. The branching of LCA was observed till their termination. Any variation in the course and branching pattern was recorded and photographed. Results: The left coronary artery most commonly originated from the left posterior aortic sinus (98%) which is the most common pattern, with only a rare origin from the anterior aortic sinus (2%). Regarding branching pattern, bifurcation was the predominant type (82%), followed by trifurcation (14%), while single and quadrifurcation patterns were uncommon (2% each). Conclusions: the present study focuses on elucidating these variations to aid in accurate diagnosis and effective therapeutic management of coronary artery disease.